Mandibular overdentures using short implants: neoteric treatment modality to reduce residual ridge resorption / Zethy Hanum Mohamed Kassim and Rohana Ahmad - Mohamed Kassim, Zethy Hanum; Ahmad, Rohana (Research Innovation Business Unit, 2014)
Excessive load and possibly altered mechanical stresses negatively impacts the alveolar ridge, prostheses and implant components when mandibular two-implant overdentures are used to treat completely edentulous patients. The debilitating effect for patients, which includes excessive residual ridge reduction in the posterior region of the mandible, has been well established. This project aims to investigate effect of new treatment modality which is the placement of additional short implants at the distal mandibular alveolar ridge to help hold the bone in this region and distribute masticatory forces over a larger area.